2001
DOI: 10.1001/archinte.161.14.1751
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Adult Cardiopulmonary Resuscitations at a Tertiary Referral Center Including Results of "Limited" Resuscitations

Abstract: Very ill patients in unmonitored beds are at increased risk for a nonwitnessed cardiac arrest and poor resuscitation outcome during the night. Closer vigilance of these patients at night is warranted. The outcome of limited resuscitation efforts is very poor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
1
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(62 citation statements)
references
References 27 publications
5
48
1
4
Order By: Relevance
“…[15,17] In the present study, the patients with total adrenaline ≤5 mg had a better ROSC, survived for 24 hours, survived to hospital discharge, or survived to discharge with favourable neurological outcomes, compared those with total adrenaline >5 mg ( P <0.01), whereas multivariate logistic regression analysis showed that total adrenaline level ≤5 mg was identified as a favorable predictor for ROSC. Currently, a larger number of trials and a randomized controlled trial[23,24] focused on outcomes of CA patients whenever adrenaline given or not.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…[15,17] In the present study, the patients with total adrenaline ≤5 mg had a better ROSC, survived for 24 hours, survived to hospital discharge, or survived to discharge with favourable neurological outcomes, compared those with total adrenaline >5 mg ( P <0.01), whereas multivariate logistic regression analysis showed that total adrenaline level ≤5 mg was identified as a favorable predictor for ROSC. Currently, a larger number of trials and a randomized controlled trial[23,24] focused on outcomes of CA patients whenever adrenaline given or not.…”
Section: Discussionmentioning
confidence: 65%
“…In a study by Dumot et al,[17] CA with witness had a 2.2 times chance for surviving to discharge, compared with CA without witness. Rafati et al[18] also reported the similar observation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unexpected in-hospital cardiac arrest is common and associated with a high mortality rate [1][2][3][4]. When cardiac arrest occurs in a general ward area, many hospitals use a "cardiac arrest team" to respond and provide immediate resuscitation.…”
Section: Introductionmentioning
confidence: 99%
“…For in-hospital SCD, intubation within 5 minutes (compared with intubation performed Ͼ5 minutes after arrest) has been associated with either worse outcome or a slight increase in 24-hour survival without increased ROSC. 85,86 Out-of-hospital data are more heterogeneous: Both intubation (regardless of timing) and intubation within 12 minutes have been associated with improved survival in retrospective studies. 87,88 On the other hand, studies assessing minimally interrupted cardiac resuscitation and passive ventilation suggest that intubation may not be advantageous.…”
Section: Timing Of Airway Interventionsmentioning
confidence: 99%